“Análisis de las Políticas Públicas en Materia de Salud Mental en el Ámbito Laboral en Ecuador” - Morales Carrión, Stefany Verona (2024)
This work arises in response to the need to study an issue that has become more prominent in recent years: public policies on mental health in the workplace. This situation has gained attention among citizens due to the lack of implementation, despite being included in our regulations. It is also linked to the absence of legal oversight to inform the Ecuadorian population about the existence of these public measures designed for their benefit. In light of this, the objective is to conduct a legal, doctrinal, and comparative analysis of public policies on mental health in the workplace. The failure to enforce these policies, established to safeguard the community's mental health, has had a noticeable impact on emotional stability, motivating the need for this analysis. In this regard, to carry out the research, an analysis of related topics was conducted to understand public policies and the reasons for their development. Additionally, surveys and interviews were conducted with various legal actors in the city of Loja to gather their perspectives on this issue. The analysis of the study's objectives regarding public policies on mental health in the workplace in Ecuador reveals several key points. The existence of public policies was identified, but also significant non-compliance due to the lack of dissemination and public awareness. 90% of respondents do not consider these policies effective, highlighting the need for greater promotion by the State. Moreover, the impact of remote work on mental health is evident, with 83.3% of 4 respondents reporting effects. The study also compares policies in Colombia, Venezuela, and Peru, emphasizing the importance of States ensuring access to mental health services. Although Ecuador's "Mental Health Law" protects these rights, its implementation has been deficient, especially in the context of the pandemic. Thus, the pressing need to analyze public policies on mental health, particularly in the workplace, was confirmed, as it has significantly affected workers' mental balance.